Penggunaan Aplikasi Media Sosial Berbasis Audio Visual dalam Membentuk Konsep Diri (Studi Kasus Aplikasi Tiktok) - Dian Novita Sari Chandra Kusuma; Roswita Oktavianti (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2020)
TikTok social media is popular with various groups and age groups. TikTok is an audio visual based social media application that contains short videos that are homemade or made by other people who entertain with interesting features such as the latest music, unique face filters and others. This study uses the Theory of Uses and Gratifications to determine individual satisfaction in using TikTok social media. Social media can shape the self-concept of its users based on internal factors (physical and psychological) and external factors (other people and reference groups). This study aims to find out how the use of audio visual-based social media in shaping the self-concept of users with different age levels. This study uses a qualitative approach with a case study method for users of TikTok social media. Data collection was carried out using observations and interviews with 4 sources of users of TikTok applications who have different age levels. The results of this study indicate differences in the age level of TikTok users affect the duration of using the application also affect the formation of self-concept formed by the speakers. The use of the TikTok application forms the self-concept of the resource person in a positive direction such as increasing the confidence of the resource person to show his identity and negative self-concepts such as lack of time management.Media sosial TikTok digemari oleh berbagai kalangan dan jenjang umur. TikTok adalah aplikasi media sosial berbasis audio visual yang berisikan video-video pendek buatan sendiri maupun buatan orang lain yang menghibur dengan fitur-fitur menarik seperti musik terbaru, filter wajah yang unik dan lain-lain. Penelitian ini menggunakan Teori Uses and Gratifications untuk mengetahui kepuasan individu dalam menggunakan media sosial TikTok. Media sosial dapat membentuk konsep diri dari penggunanya berdasarkan faktor internal (fisik dan psikis) dan faktor eksternal (orang lain dan kelompok rujukan). Penelitian ini bertujuan untuk mengetahui bagaimana penggunaan media sosial berbasis audio visual dalam membentuk konsep diri penggunanya dengan jenjang umur yang berbeda. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus terhadap pengguna media sosial TikTok. Pengumpulan data dilakukan menggunakan observasi dan wawancara kepada 4 narasumber pengguna aplikasi TikTok yang memiliki jenjang umur yang berbeda. Hasil dari penelitian ini menunjukkan perbedaan jenjang umur pengguna TikTok mempengaruhi durasi dalam menggunakan aplikasi juga mempengaruhi pembentukan konsep diri yang dibentuk oleh narasumber. Penggunaan aplikasi TikTok membentuk konsep diri narasumber ke arah positif seperti meningkatkan kepercayaan diri narasumber untuk menunjukkan jati dirinya dan konsep diri negatif seperti kurangnya dalam mengatur waktu.